Manifestação da cultura corporal no residencial Buena Vista: um estudo amparado na compreensão espacial de Milton Santos - Souza, Samuel Gomes de (2025)
This dissertation aimed to identify the relationships between the territory and Body Culture in the sport, health, and leisure activities of the population of Residencial Buena Vista, Goiânia, Goiás. To this end, it presents the history of the territory from its production and social occupation; identifies and characterizes spatial roughnesses (created by the government, organizations, individuals, or institutions) related to Body Culture in sport, health, and leisure; analyzes the population's relationship with these roughnesses, actions, and activities to promote Body Culture in the territory; and identifies and contextualizes the problems, needs, and potential of the territory related to the production and manifestation of Body Culture in the population of Residencial Buena Vista. As a qualitative study, it assumes that Body Culture is also determined by the dialectical relationship between people and space, which is produced by particular and universal mediations: space being a historical and social instance. Therefore, the problem of this research was summarized with the question: how does the relationship between territory and the process of production and manifestation of Body Culture in the population of Residencial Buena Vista occur? Thus, it presumes the relationship between territory and the production and manifestation of Body Culture in a particular and universal, local and global, everyday and historical way. In view of this, the need arose to study the set of Body Practices materialized in local social praxis, starting with space as the central category, through a methodological organization that begins with a documentary survey on the history of the neighborhood and its population, followed by an empirical study in Residencial Buena Vista. This research combined different data collection instruments, with the subjects being residents or workers in the neighborhood, encompassing the following stages of empirical research: field observation; focus groups; and interviews.